If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20.8 = -6(2.7x + -0.8) Reorder the terms: -20.8 = -6(-0.8 + 2.7x) -20.8 = (-0.8 * -6 + 2.7x * -6) -20.8 = (4.8 + -16.2x) Solving -20.8 = 4.8 + -16.2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16.2x' to each side of the equation. -20.8 + 16.2x = 4.8 + -16.2x + 16.2x Combine like terms: -16.2x + 16.2x = 0.0 -20.8 + 16.2x = 4.8 + 0.0 -20.8 + 16.2x = 4.8 Add '20.8' to each side of the equation. -20.8 + 20.8 + 16.2x = 4.8 + 20.8 Combine like terms: -20.8 + 20.8 = 0.0 0.0 + 16.2x = 4.8 + 20.8 16.2x = 4.8 + 20.8 Combine like terms: 4.8 + 20.8 = 25.6 16.2x = 25.6 Divide each side by '16.2'. x = 1.580246914 Simplifying x = 1.580246914
| 10x-(8x-7)=67 | | 0.25r-0.25+-.25r=0.5-0.25r | | 3.7x+2.3x+6=6x+8-2 | | -165+n= | | 5x^2+29x+20=0 | | -10a+4=-a-14 | | 3x+(x+8)=180 | | 23=q+-74 | | 23 = q+ -74 | | (2n+4)+(3n-2)=8n-19 | | 4(x+10)=50 | | 3(4x-7)=-21+12z | | 9s^2-324s+648=0 | | 7(3-3m)-(8m-4)=54 | | 6-2[3-(2y-2)]= | | -5y-7=2y-14 | | 8x-8x=10+1+2x-3 | | 2x-15=3x+29 | | 5y+2(3-y)=5+3y+2 | | 20-3n=7n | | (2x+10)(3x+5)= | | b^2+3b-88=0 | | -11+x-9=1-2x | | -6x+7=3(3-2x)-2 | | 54-8=3y+12 | | 3x^3+x^2+15x+5= | | ac=-99 | | 9x-5=-23 | | 14=-(p-4) | | 3(-3-5r)=-2(1-6r)+8 | | 15=2(2t-1) | | a+18=-43 |